Well-being in later life: a life course perspective - Pattharanitcha Prakitsuwan (2020)
© 2020, Emerald Publishing Limited. Purpose: This study aims to illustrate the viability of the life course paradigm (LCP), which is increasingly used by social and behavioral scientists to study a wide variety of phenomena, as a framework for studying the transformational role of service consumption in improving consumer well-being in later life. Design/methodology/approach: The LCP is used to develop a life course model for studying the effects of service consumption on older people’s well-being. Previous research related to the consumption of specific types of services (financial and healthcare) is integrated within the multi-theoretical LCP to suggest relevant model variables and derive a set of propositions for illustrating the effects of service consumption on older adults’ well-being. Findings: The research presented in this study shows how efforts to study the effects of service consumption on older people’s well-being can be improved by using the LCP, helps understand the onset and changes in service consumption patterns and illustrates an innovative way to study the role of services in promoting older consumer welfare. Originality/value: By applying the principles and theoretical perspectives of the LCP, this study contributes to recent transformative service research efforts to better understand the impact of service consumption on people’s lives and the transformational role of services and service providers in improving consumer and societal welfare.